Taking stock of oral history archives in a village in KwaZulu-Natal province, South Africa: Are preservation and publishing feasible? - Zimu-Biyela, Acquinatta N. (HTS teologiese studies, 2022)
In South Africa, the way oral history archives of rural villagers are managed calls for attention as it can limit the inclusivity, visibility, accessibility and socio-economic development of rural communities, especially the younger generation. This article reports on a study that aimed to unpack some of the opportunities and challenges regarding the preservation and publishing of oral history archives faced by a village community in the KwaZulu-Natal (KZN) province. In addition, the study aimed to determine what the community knew about the South African legislative requirements regarding the management of oral history archives. The study adopted a qualitative research approach, grounded theory design and a constructivist paradigm. The postmodernist theory helped in gaining insight into how the principle of provenance is central when trying to understand the importance of inclusivity in the management of archives in this digital era. The 21st century is haunted by many socio-economic challenges such as the coronavirus disease 2019 (COVID-19), poverty, unemployment, inequality and social exclusion and giving space to the long-neglected oral history archives and counter archives or identity archives cannot be over-emphasised. In this context, such an initiative is viewed as critical in curbing the scourges of inequality, social exclusion and unemployment, particularly among the younger generation.Contribution: This article calls for the reimagining of the way oral history archives of a village are managed, preserved and published. In doing so, the use of a postmodernist approach and the provenance principle are viewed as critical in helping promote inclusivity and visibility of the long-neglected archives. The article argues that this approach may also help improve some of the socio-economic challenges faced by a village community when managing their oral history archives.